Advancing Early Detection of Major Depressive Disorder Using Multisite Functional Magnetic Resonance Imaging Data: Comparative Analysis of AI Models - Masab Mansoor; Kashif Ansari (JMIRx Med, 2025)
Abstract BackgroundMajor depressive disorder (MDD) is a highly prevalent mental health condition with significant public health implications. Early detection is crucial for timely intervention, but current diagnostic methods often rely on subjective clinical assessments, leading to delayed or inaccurate diagnoses. Advances in neuroimaging and machine learning (ML) offer the potential for objective and accurate early detection. ObjectiveThis study aimed to develop and validate ML models using multisite functional magnetic resonance imaging data for the early detection of MDD, compare their performance, and evaluate their clinical applicability. MethodsWe used functional magnetic resonance imaging data from 1200 participants (600 with early-stage MDD and 600 healthy controls) across 3 public datasets. In total, 4 ML models—support vector machine, random forest, gradient boosting machine, and deep neural network—were trained and evaluated using a 5-fold cross-validation framework. Models were assessed for accuracy, sensitivity, specificity, F1 ResultsThe deep neural network model demonstrated superior performance with an accuracy of 89% (95% CI 86%‐92%) and an area under the receiver operating characteristic curve of 0.95 (95% CI 0.93‐0.97), outperforming traditional diagnostic methods by 15% (P ConclusionsOur findings highlight the potential of artificial intelligence–driven approaches for the early detection of MDD, with implications for improving early intervention strategies. While promising, these tools should complement rather than replace clinical expertise, with careful consideration of ethical implications such as patient privacy and model biases.